Modeling of the polyethylene chlorination process; a problem – oriented process simulator - Kun, Gabriella; Chován, Tibor; Nagy, Lajos; Szeifert, Ferenc; Czeller, Attila; Tóth, Attila (Acta Agraria Kaposváriensis, 2004)
Chlorinated polyethylene (CPE) is a widely used, inherently soft polymer. The final properties of chlorinated polyethylene depend on the molecular and phase structure controlled by chlorination conditions. Present market situation justifies studying the possibilities for the extension of CPE production. To support this work a simulator of the chlorination technology was developed. In the paper, beside the introduction of the CPE process, the details of our modeling approach and the structure of the applied simulator package are discussed. This package allows supporting the process development steps by describing the involved thermodynamic phases and components as well as their interactions (reactions, heat and mass transfer etc.). The simulator package consists of three modules: a reactor simulator, a reaction-kinetic simulator and an identification module.
Keywords: chlorinated polyethylene; tendency model; process simulator